SAT0074 Smoking Cessation Significantly Reduces Failure of BIOLOGICS (BIO)-Treatment in Rheumatoid Arthritis (RA): from the "Ninja" Registry Cohort of Japanese Patients. (10th June 2014) - Saeki, Y.; Matsui, T.; Kagawa, K.; Ohshima, S.; Matsushita, M.; Tanaka-Kudo, E.; Tsuji, S.-I.; Yoshimura, M.; Watanabe, A.; Teshigawara, S.; Katayama, M.; Katada, Y.; et al.
Abstract : Background: Biologics (Bio) targeting cytokines and lymphocytes have shown outstanding efficacy and become a master of drug in the treatment of rheumatoid arthritis (RA). However, some issues remain to be addressed and resolved, including adverse effects (AE) such as serious infections, therapeutic failure (Failure) and high cost. On the other hand, cumulative evidence has suggested that some genetic and environmental factors might affect responsiveness of anti-rheumatic drugs, including Bio. Smoking is thought to be one of crucial environmental factors. Objectives: To investigate the influence of smoking on Bio-treatment in RA, the association between the causes of discontinuation of Bio and smoking was analyzed by using the data from the "NinJa" Registry cohort of Japanese RA patients. Methods: The causes of discontinuation of Bio-use were analyzed by using the data of the "NinJa" from 2007 to 2012. The "NinJa" Registry is one of the largest Japanese RA patient cohort and now consists of the clinical data of 11, 940 patients from more than 30 hospitals. Smoking habit was assessed by a questionnaire (60.1% of the total patients answered) and the patients were divided into three groups as smoking, non-smoking, smoking cessation. The association between the causes of discontinuation of Bio (Failure, AE, Remission) and smoking habit was analyzed statistically and shown as odds ratio (OR). Results: 3, 187 (26.7%) of the total registered patients were treated with one or more Bio during 6 years. Among them, 584 (18.3%), 1, 321 (41.4%), 397 (12.5%), 589 (18.5%), 223 (7.0%), and 73 (2.3%) of the patients were treated with IFX, ETN, ADA, TCZ, ABT and GLM respectively. The total numbers and percentages of discontinuation of Bio-use were 335 (57.4%), 418 (31.6%), 220 (55.4%), 162 (27.5%), 65 (29.1%) and 42 (57.5%) in IFX, ETN, ADA, TCZ, ABT and GLM respectively. The causes of discontinuation were analyzed according to four categories, Failue, AE, Remission, and others. The association between the causes of discontinuation of Bio (Failure, AE, Remission) and smoking habit was shown in Table. Failure in the smoking group was significantly more frequent compared to both in the non-smoking and smoking cessation groups. Conclusions: In RA, smoking habit might affect responsiveness of Bio-treatment and in addition smoking cessation might reduce failure of Bio-treatment. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1441